The Accounting Determinants Of Cash Holdings During Inflation /A Survey Study On Non-Financial Companies Registered In The Securities And Syrian Markets Commission/ (Latakia University Journal - Economic and Legal Sciences Series, 2022)
This research aims to study the accounting determinants of monetary assets of non-financial companies registered with the Syrian Commission for Securities and Financial Markets. The research was based on 11 non-financial companies registered for the period from 2010 to 2020, and the published lists of these companies were relied upon to measure the variables. In this research, the observations were divided into two subgroups based on the first time frame, which reflects the period of limited inflation, which is the period prior to 2014 and the second reflects the period of hyperinflation, which is the period following this year. The results showed that in the period of limited inflation, capital expenditure and cash flow were the determinants of monetary assets, while working capital, financial leverage and growth opportunities each had a non-statistically significant effect on monetary assets. During inflation, working capital, financial leverage and capital expenditure became determinants of monetary assets with a statistically significant inverse effect, in addition to cash flow with a direct statistically significant effect.